Preparation and Application of Nanozymes with Uricase‐Like Activity Based on Molecularly Imprinted Polymers. Issue 1 (2nd January 2023) - Liu, Donghao; Yi, Simin; Ni, Xu; Zhang, Jingjing; Wang, Fangqi; Yang, Ping; Liu, Meiru; Peng, Jun; Dramou, Pierre; He, Hua
Abstract: Nanozymes have advantages over natural enzymes in terms of efficiency, stability, and economy. MVSM (Mixed Valence State MOF) is a nano‐oxidase with uricase‐like activity that may catalyze uric acid (UA) in the body into allantoin and H2 O2 to treat gout and hyperuricemia by substituting natural uricase. However, it cannot specifically identify and choose UA. To increase the selectivity and affinity of MVSM for UA, the composite material MVSM@MIP is innovatively synthesized using a new synthetic approach termed the "two‐step synthesis method, " which may prevent UA from being oxidized by MVSM during manufacture in this study. At the same time, this study also provides experimental proof of the effective creation of the material, the advantages of the "two‐step synthesis approach, " and the high selectivity and affinity of MVSM@MIP for UA. Based on these findings, the suggested technique may be used to effectively catalyze uric acid in human urine with high activity. Abstract : Prepared method and adsorption process : MVSM and MIPs were combined to create molecularly imprinted nanozymes that outperform oxidase mimics. At the same time, we developed a novel "two‐step synthesis method" for producing the composite material MVSM@MIP and deduced the catalytic mechanism of MVSM@MIP for UA (see picture).